2021
DOI: 10.1111/ijac.13761
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polyacrylic acid (PAA)/Na2HPO4 mixture on biphasic calcium phosphate cement: Enhancing strength and cell viability

Abstract: This study has investigated the effect of combination of new liquid phase mixture of disodium hydrogen phosphate (Na 2 HPO 4 ) and polyacrylic acid (PAA) on the compressive strength, setting time, bioactivity, and cytotoxicity of biphasic calcium phosphate cement. The PAA was known as one of water-soluble and biocompatible polymers to improve the mechanical performances of the bone cement, but it usually inhibits the phase conversion to hydroxyapatite after the cement has already set.The aim of this work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(82 reference statements)
2
3
0
Order By: Relevance
“…Thus, the porosity of samples could be related to the phase transformation and the degradation. Based on phase transformation, it was reported that the PAA could cover the surface of the cement powder, resulting in less α‐TCP phase conversion into HA 16 . This is correlated to the current work, presenting the less converted HA phase in PAA incorporated cement (p‐CPC), as compared with the control CPC from 0 to 28 day.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, the porosity of samples could be related to the phase transformation and the degradation. Based on phase transformation, it was reported that the PAA could cover the surface of the cement powder, resulting in less α‐TCP phase conversion into HA 16 . This is correlated to the current work, presenting the less converted HA phase in PAA incorporated cement (p‐CPC), as compared with the control CPC from 0 to 28 day.…”
Section: Discussionsupporting
confidence: 86%
“…Based on phase transformation, it was reported that the PAA could cover the surface of the cement powder, resulting in less α-TCP phase conversion into HA. 16 This is correlated to the current work, presenting the less converted HA phase in PAA incorporated cement (p-CPC), as compared with the control CPC from 0 to 28 day. In addition, the presence of PAA appeared to interfere and encapsulate some of the DCPA particles, resulting in the more DCPA remaining in the cement matrix of p-CPC and p-CPC/BG when compared with the control CPC (Figure 9C).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…PMA is also used to improve the mechanical properties of calcium phosphate cement. To optimize the properties of bone cement for medical application, Thaitalay et al studied the cement solution at different v / v % ratio of Na 2 HPO 4 and PAA [ 128 ]. The best ratio was found to be 30:70 v / v % (PAA: Na 2 HPO 4 ), improving the compressive strength and reaching a high cell viability, while the phase transformation is kept for bioactivity giving a suitable composite as bone substitution material.…”
Section: Polyacrylate: Applicationsmentioning
confidence: 99%